2004
DOI: 10.1042/bst0320231
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct pathways for thymidylate (dTMP) synthesis in (hyper)thermophilic Bacteria and Archaea

Abstract: The hyperthermophilic anaerobic archaeon Pyrococcus abyssi, which lacks thymidine kinase, incorporates label from extracellular uracil, but not from thymidine, into its DNA. This implies that P. abyssi must synthesize dTMP (thymidylate), an essential precursor for DNA synthesis, de novo. However, iterative similarity searches of the three completed Pyrococcus genomes fail to detect candidate genes for canonical thymidylate synthase ThyA, suggesting the presence of alternative pathways for dTMP synthesis. Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…ThyX proteins represent a recently discovered family of flavoproteins, essential for DNA replication in at least 30% of the microbial genomes sequenced to date [the considerable biases in available genome sequences underestimate this number (14)]. During this work we have undertaken structure-function studies on the functional roles of conserved ThyX amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…ThyX proteins represent a recently discovered family of flavoproteins, essential for DNA replication in at least 30% of the microbial genomes sequenced to date [the considerable biases in available genome sequences underestimate this number (14)]. During this work we have undertaken structure-function studies on the functional roles of conserved ThyX amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…All the Borrelia sp. proteins have the ThyX motif of RHRX 7 S (positions 90 to 100 of B. hermsii ThyX) that is common to these proteins at their conserved amino-terminal domain (30,35). The gene products of B. hermsii and B. burgdorferi share the following residues in common with other ThyX orthologues (B. hermsii ThyX numbering): H65, E70, F76, R90, H91, R92, S100, Y103, E168, R171, L174, P175, L197, R198, E206, R208, A211, and P223 (29).…”
Section: Vol 188 2006mentioning
confidence: 99%
“…In other species of organisms, the thyX product, ThyX, is thymidylate synthase X (EC 2.1.1.148), which catalyzes the methylation of dUMP to yield the DNA precursor dTMP. Sequences homologous to thyX have been found in several groups of bacteria, including cyanobacteria, actinobacteria, and epsilonproteobacteria such as Helicobacter pylori, but they are also present in some double-stranded DNA viruses of bacteria and at least one eukaryote, the slime mold Dictyostelium discoides (30,35). Other groups of bacteria, including gamma-proteobacteria such as Escherichia coli and firmicutes such as Bacillus subtilis, usually have instead a thyA gene, which encodes thymidylate synthase A (ThyA; EC 2.1.1.45) and is not homologous to thyX (11,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation led to the identification of alternative flavin-dependent thymidylate synthases (FDTSs), which are encoded by the thyX gene and have no sequence or structure homology to classic TSase enzymes (2,6,7). Furthermore, multiple studies have identified key differences in the molecular mechanism of catalysis between FDTSs and classic TSases (2,4,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These differences, along with the fact that the thyX gene is present in many human pathogens (e.g., bacteria causing Anthrax, Tuberculosis, Typhus, and other diseases), renders these flavo-enzymes as potential targets for rational inhibitor design, possibly affording compounds that might be effective antimicrobial drugs (11,(22)(23)(24).…”
mentioning
confidence: 99%